2019
DOI: 10.1177/1559325819874897
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Protective Mechanisms of Dandelion Leaf Extract Against Cisplatin-Induced Nephrotoxicity in Rats: Role of Inhibitory Effect on Inflammatory and Apoptotic Pathways

Abstract: Cisplatin (CP) nephrotoxicity is associated with the induction of oxidative stress, inflammation, and apoptosis. Several studies demonstrated the antioxidant, anti-inflammatory, and antiapoptotic effects of dandelion leaf extract (DLE); therefore, this research aimed to investigate the protective effects of DLE against CP-induced nephrotoxicity. Thirty-two male Wistar rats were divided into 4 groups: normal control, DLE control received 500 mg/kg daily for 11 days, intoxicated group received vehicle daily for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…This is mostly associated with the production of ROS, which damages mitochondrial membrane lipids and culminates in increased caspase-3 activity. Additionally, nephroprotection mediated by various pharmacological modalities is associated with a reduction in caspase-3 activity [ 26 , 27 , 28 , 29 , 30 ], further confirming the role of caspase-3 in Cp-induced nephrotoxicity [ 26 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 75%
“…This is mostly associated with the production of ROS, which damages mitochondrial membrane lipids and culminates in increased caspase-3 activity. Additionally, nephroprotection mediated by various pharmacological modalities is associated with a reduction in caspase-3 activity [ 26 , 27 , 28 , 29 , 30 ], further confirming the role of caspase-3 in Cp-induced nephrotoxicity [ 26 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 75%
“…Dandelion leaf extract treatment improved cisplatin‐induced nephrotoxicity and increased cisplatin‐induced elevations in serum creatinine, blood urea nitrogen, and oxidative stress markers. Dandelion extract has a promising nephroprotective effect through antioxidant, anti‐inflammatory, and antiapoptotic effects 63 . Dandelion has been used extensively as a diuretic in phytotherapy without a prior clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Dandelion extract has a promising nephroprotective effect through antioxidant, anti-inflammatory, and antiapoptotic effects. 63 Dandelion has been used extensively as a diuretic in phytotherapy without a prior clinical trial. Clare et al 64 investigated the effect of dandelion extract intake on increased frequency and volume of urination.…”
Section: Discussionmentioning
confidence: 99%
“…In a study where different dandelion leaf methanol extracts (250, 500 and 750 mg/kg) were examined for cisplatin nephrotoxicity, it was stated that all doses reduced serum creatinine and urea levels (the most effective dose; 500 mg/kg) and the extract did not have any side effects [47]. Dandelion extracts applied in different doses against nephrotoxicities caused by various chemicals (CCl4, cisplatin, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Dandelion, which is widely found in the world, has a diuretic effect, and this is attributed to the richness of sesquiterpene lactone content [60]. In a rat study where dandelion leaves methanol extract (500 mg/kg) was applied against cisplatin nephrotoxicity; it was reported that the extract increased SOD activity and GSH level and further decreased LPO level [47]. In an experiment given dandelion extract (100 mg/kg) against kidney damage caused by carbon tetrachloride in rats; it lowered the level of MDA, but there was no statistical difference in GSH and GPx level/activity [49].…”
Section: Discussionmentioning
confidence: 99%